A giant aneurysm of the left main coronary artery and anomalous origin of the right coronary artery - Özkan, Hakan (Kardiochir Torakochirurgia Pol, 2015)
We report a rare case of a giant aneurysm of the left main coronary artery (LMCA) and anomalous origin of the right coronary artery (RCA) from the left ventricle presented with chest pain.